O Little Town of Bethlehem N.M. - Seidman, Carrie (Cimarron, New Mexico Cimarron Legend, 1992)
Newspaper article on the City of Bethlehem in Raton, New Mexico.
Master list item #: 35
File location is in the Raton file Cabinet
Keywords: Brown, Wesley; Karlin, Glen; Woodsworth, Woody; Gonzales, Robert; The Lions Club; Raton Public Service; Pittsburgh and Midway Coal and Mining Company; Local History; Display History; Christmas Exhibits; Holiday Traditions; Drive Through Exhibits; Christmas Lights; Raton, New Mexico; City of Bethlehem; Climax Canyon; Apache Avenue; Sangre de Christo; Santa Fe, New Mexico; Albuquerque, New Mexico; Madrid, New Mexico